2013
DOI: 10.1177/000313481307900615
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Hepatectomy is a Safe and Effective Approach for Resecting Large Colorectal Liver Metastases

Abstract: Hepatectomy is an accepted treatment modality for large (greater than 5 cm) colorectal liver metastases (CLM). Recently, laparoscopic hepatectomy has emerged as a viable option; however, its use for patients with large CLM is undefined. A retrospective analysis of a single institution's prospective database was performed for patients with large CLM resected between 1995 and 2010. Patients were stratified by operative approach. Patient characteristics, tumor burden, operative factors, hospital course, and long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…A perioperative blood transfusion was required in 14.6% of the patients. In other laparoscopic series, the rate of blood transfusion ranges between 3.4% and 30% .…”
Section: Discussionmentioning
confidence: 95%
“…A perioperative blood transfusion was required in 14.6% of the patients. In other laparoscopic series, the rate of blood transfusion ranges between 3.4% and 30% .…”
Section: Discussionmentioning
confidence: 95%
“…After a mean follows up of 32 months, disease-free survival and overall survival were 40.2 and 23.3 months for the laparoscopic group, and 47.7 and 31.4 months for OR group (PNS) [5]. In other studies looking specifically at LLS, the vast majority of these aforementioned clinical benefits were replicated [1,2,4,[6][7][8][9][10][11][12]. Figueredo and Yeung concluded that LLR reduced pain, inpatient days with more or less comparable operative outcome.…”
Section: Discussionmentioning
confidence: 96%
“…Laparoscopic resection appears to be a safe approach for resecting large CLM. Tumor size does not preclude laparoscopic hepatectomy [7]. LLR can be safely adopted today especially for lesions in the anterolateral segments.…”
Section: Variables Llr(n=102) Olr(n=198) P Valuementioning
confidence: 99%
“…Laparoscopic hepatectomy (LH) was introduced in 1995 and has presented challenges because of the diversity of tumor locations and the complexity of the liver . Recent technological advancements in surgical devices have contributed to the increased use of LH for treating liver malignancy . Compared with open hepatectomy, the laparoscopic procedure provides several benefits associated with a minimally invasive procedure, including less postoperative pain, reduced morbidity, and faster recovery .…”
Section: Introductionmentioning
confidence: 99%
“…Recent technological advancements in surgical devices have contributed to the increased use of LH for treating liver malignancy . Compared with open hepatectomy, the laparoscopic procedure provides several benefits associated with a minimally invasive procedure, including less postoperative pain, reduced morbidity, and faster recovery . However, there are some obstacles to the wider acceptance of LH, such as the lack of suitable laparoscopic ultrasound techniques for liver segment staining.…”
Section: Introductionmentioning
confidence: 99%